2016
DOI: 10.5430/jnep.v6n8p74
|View full text |Cite
|
Sign up to set email alerts
|

Learning effectiveness of nurses caring for patients with pulmonary artery catheters using e-learning and simulation approaches

Abstract: Background: A systematic training program has not been developed for pulmonary artery catheter (PAC) patient care in Taiwan; only the mentor-apprentice learning approach is used. Therefore, it is difficult for nursing personnel to maintain mastery of care. Methods: ICU nurse practitioners of regional teaching hospitals were enrolled in this study to perform pretest, post-test, and repeated measurements in order to examine the long-term learning effectiveness of this intervention. Before and after e-learning us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Learning methods such as case studies, simulation, group discussion, and reflection can be used to enhance clinical reasoning skills in nursing education. 52 Moreover, mastery learning method 53 and simulation approaches 14 can be used to teach practical skills to nurses. The findings indicated that the development of continuing education programs in the area of clinical reasoning skills for hemodynamic monitoring should be more emphasized on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning methods such as case studies, simulation, group discussion, and reflection can be used to enhance clinical reasoning skills in nursing education. 52 Moreover, mastery learning method 53 and simulation approaches 14 can be used to teach practical skills to nurses. The findings indicated that the development of continuing education programs in the area of clinical reasoning skills for hemodynamic monitoring should be more emphasized on.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, they have suggested educational hemodynamic monitoring. 13,14 The undesirable level of knowledge and the application of vital systems assessment skills by nurses can also be attributed to some factors such as method of training, lack of retraining, inadequate supervision of nurses' practice, and the routine nursing practices in Iran. 15 Educational needs assessment should be addressed to modify an effective educational status to meet information and challenges faced in the clinical setting.…”
mentioning
confidence: 99%